Online loan moderation: Hedonism and consumptive behavior - Dedeh Kurniasih (Jurnal Mantik, 2023)
In the technological era, several conveniences in activities include making loans, in this case, online loans. The aim of this research is to test the moderating effect of online loans on hedonism on consumer behavior. This research uses a causality approach with PLS-SEM; the population in this research is active students in Serang City, with a sample of 392 respondents. The results of this research show that hedonism has a significant influence on consumer behavior and also a significant impact on the desire to make online loans. Meanwhile, online loans are a moderating variable in hedonism towards consumer behavior